Bio-cementation for Slope Soil Stabilization against Surface Erosion: A Bench-scale Preliminary Investigation - Gowthaman, S.; Nakashima, K.; Ebina, K.; Kawasaki, S. (American Rock Mechanics Association (ARMA), 2019)
Surface instability of residual soil slope due to erosion is one of the widespread issues all over the world. Bio-cementation is a novel soil improvement method, wherein urease-producing bacteria or urease enzyme can be used to bind sand particles through calcite formation, enhancing the engineering properties of soil. This research work aims to assess the feasibility of bio-cementation technique as a potential alternative for surface stabilization of the slopes. A residual slope soil (Hokkaido, Japan) was instrumented in bench-scale slope for solidification test at the laboratory. Native ureolytic bacteria was enriched under optimum environmental conditions and injected to percolate through slope surface, followed by number of injections of cementation solution. The results indicated that relatively a stiff layer/ crust (69 MPa) with the thickness ranging from 3-4 cm is found along the slope surface. However, the UCS values decreased with the depth of the slope. The hydraulic conductivity of the slope soil reduced from 1.9×10-2 cm/s to 1.85×10-3 cm/s (by 90%) due to the cementation, which could inhibit the excess infiltration of rainwater and enhance the surface runoff.
Keywords: Slope surface stabilization; Bio-cementation; Surface percolation; Native ureolytic bacteria; Calcium carbonate content